The influence of exclusive breastfeeding on the incident of stunting - Sukmawati, Ellyzabeth (Institute of Computer Science (IOCS), 2024)
This study aims to investigate the relationship between exclusive breastfeeding and the incidence of stunting in children. This type of research is quantitative. Research data uses primary data and secondary data. Primary data from questionnaires and observation sheets. Secondary data from journals, books and respondent health data. Data analysis was carried out using the chi-square test to determine the relationship between exclusive breastfeeding and the incidence of stunting. Based on the analysis results, if seen from the sig. chi-square table is greater than 0.05, it can be said that Ho is rejected and Ha is accepted. Thus, it can be concluded that there is a relationship between exclusive breastfeeding and the incidence of stunting. It is hoped that the results of this research can be used as a basis for developing effective intervention programs in dealing with stunting problems in society.